Sediment Carbon Stocks and CO₂ Sequestration Capacity in the Bagek Kembar Mangrove Essential Ecosystem Area, West Lombok - Eni Suyantri; Gito Hadiprayitno; Didik Santoso; Karnan; M. Liwa Ilhamdi; Pahrurrozi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to analyze and compare sediment organic carbon stocks, bulk density, and estimated carbon dioxide (CO₂) sequestration in natural and revegetated mangrove areas within the Bagek Kembar Mangrove Essential Ecosystem Area (KEE), Sekotong, West Lombok. Sediment samples were collected to a depth of 100 cm and analyzed using the Loss on Ignition (LOI) method. The results showed that bulk density ranged from 1.19 to 1.50 g/cm³ and tended to decrease with increasing sediment depth. Sediment organic carbon stocks were higher in the natural mangrove area (591.49 Mg C/ha) than in the revegetated mangrove area (575.39 Mg C/ha), with the greatest carbon accumulation observed at depths of 61–100 cm. This difference indicates that natural mangroves have a slightly greater capacity for carbon accumulation than revegetated areas, likely due to more stable stand structure and sediment dynamics. Estimated CO₂ sequestration followed a similar pattern, reaching 2,170.55 Mg CO₂/ha in the natural mangrove area and 2,111.68 Mg CO₂/ha in the revegetated mangrove area. These findings provide a scientific contribution by addressing data gaps on sediment organic carbon stocks and estimated CO₂ sequestration in mangrove ecosystems in Lombok. They also strengthen the basis for conservation- and restoration-oriented management to support climate change mitigation in coastal ecosystems.